2007
DOI: 10.1539/joh.49.399
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐Acquired Serogroup A Meningococcal Meningitis

Abstract: L a b o r a t o r y -A c q u i re d S e ro g ro u p A Meningococcal Meningitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several studies have reported clinical laboratory acquired meningococcemia [32]–[38]. These reports focussed on tracing the infecting strain amongst those manipulated by the patient during the weeks before the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported clinical laboratory acquired meningococcemia [32]–[38]. These reports focussed on tracing the infecting strain amongst those manipulated by the patient during the weeks before the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 16 cases of probable laboratory-acquired meningococcal disease were identified nationwide between the years 1985-2001; the vast majority of cases (15/16; 94%) arose in clinical microbiologists manipulating isolates without respiratory protection (14). The increased rates of laboratory-acquired meningococcal disease-as well as other infectious diseases-have been reported by multiple other authors as well (15)(16)(17)(18)(19). Within the US it is estimated that the incidence of meningococcal disease among microbiologists is 50fold higher than in the general population, i.e., 13 per 100 000 persons versus a general incidence rate of 0.2 per 100 000 (14,15,20).…”
Section: At Risk Populationsmentioning
confidence: 97%
“…At that point, the student denied vaccination and admitted to subculturing five isolates of serogroup A out on the bench. Fortunately, he recovered completely (Kessler, 2007).…”
Section: Karen B Byersmentioning
confidence: 98%